Passive Ceiling Light Disinfection System to Reduce Bioburden in an Intensive Care Unit - Rohan, Annie; Khan, Imraan; Yin, Donglei; Yang, Jie (Journal of Pediatric Intensive Care, 2019)
A ceiling-installed narrow spectrum (402–420 nm) bactericidal blue light disinfection system was installed in a large suburban medical intensive care unit (ICU) and evaluated for implementation feasibility and effectiveness in reducing environmental bioburden. Installation of 54 ceiling devices was accomplished at low cost and with minimal ICU process disruption. Postinstallation high-touch surface colony counts were significantly lower than preinstallation. Linear mixed modeling demonstrated a 21% average overall decrease in colony count after installation, with consistent reduction in colony counts starting from week 4 postinstallation. Automated technology is potentially more efficient in reducing environmental bioburden in the acute care setting compared with other bioburden reducing methods or can provide a robust compliment to manual cleaning.
Keywords: bioburden; blue light technology; infection prevention; infection control; light therapy